Spices and Condiments in Ghana: Their Utilization in Comminuted Meat Products - Sarah, Darkwa (Asian Journal of Agriculture and Rural Development, 2013)
Local spices were collected from seven major markets across Ghana, compiled and identified by their Scientific, Common and Local names, properties, part used and area found. Seven fresh pork sausages prepared using differing compositions of these spices were sensorily evaluated in a pre-trial and four selected and further evaluated in triplicate to determine their acceptability. A 10 member panel assessed the external appearance of uncooked products, internal colour, aroma, taste and the overall acceptability of cooked products. The data was analysed as a completely randomized block design using the nonparametric analysis as employed in Friedman’s method and Wilcoxon’s signed rank test. A total of fourteen local spices were collected. A 1.52% level of inclusion of the different composite spice mixes in the products was acceptable. The prekese based product was significantly judged the most acceptable (P=.05) while the dawadawa based product the least acceptable. In conclusion, preparing Ready to use composite-spice mixes from local spices to promote comminuted meat processing among meat handlers is feasible but must be done safely in order to keep the health value of the meat products.